Robustness of topologically protected transport in graphene–boron nitride lateral heterostructures. (29th December 2016) - Abergel, D S L
Abstract: Previously, graphene nanoribbons set in lateral heterostructures with hexagonal boron nitride were predicted to support topologically protected states at low energy. We investigate how robust the transport properties of these states are against lattice disorder. We find that forms of disorder that do not couple the two valleys of the zigzag graphene nanoribbon do not impact the transport properties at low bias, indicating that these lateral heterostructures are very promising candidates for chip-scale conducting interconnects. Forms of disorder that do couple the two valleys, such as vacancies in the graphene ribbon, or substantial inclusions of armchair edges at the graphene–hexagonal boron nitride interface will negatively affect the transport. However, these forms of disorder are not commonly seen in current experiments.